Reforço radicular com materiais resinosos e emprego de pinos de fibra em restaurações diretas de resina composta - Bueno, Tamires de Luccas [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The pins are being used widely in clinical endodontically treated teeth, with the coronal tooth structure is insufficient to retain the final restoration, and are used as a central support element. But the destruction of dental tissue can reach much of the root dentin, which undermines the ideal job of restraint systems. To solve this problem Adhesive restorative materials have been employed in order to strengthen the root conduit and enable the use of pins. This paper will present cases where the conduct root was reinforced by the technique adhesive with ionomer material or composite resin and in the same sitting clinin the tooth was restored with pre-manufactured pins and restorative materials. Was found in controls that the postoperative adhesive materials and restraint systems were effective in restoring the function and aesthetic form

Os pinos vêm ganhando uma ampla utilização clínica em dentes endodonticamente tratados, cuja estrutura dentária coronária é insuficiente para reter a restauração definitiva. Porém a destruição de tecido dental pode atingir grande parte da dentina radicular, o que compromete o emprego ideal desses sistemas de retenção. Para solucionar este problema materiais restauradores adesivos têm sido empregados com o intuito de reforçar o conduto radicular e possibilitar a utilização dos pinos. Este trabalho apresentará caso clínico em que o conduto radicular foi reforçado pela técnica adesiva com material ionomérico ou resina composta e, na mesma sessão clínica o dente foi restaurado com pinos pré-fabricados e materiais restauradores diretos. Foi constatado nos controles pós-operatórios que os materiais adesivos e sistemas de retenção foram eficazes para restabelecer a função a forma e a estética
Keywords: Resinas compostas; Estética dentária; Pinos dentários; Materiais restauradores do canal radicular; Composite resins